Views of the School Administrators on Their Own Professional Development and Their Leadership Behaviours for the School Improvement - Soner Polat; Celal Teyyar Uğurlu; Mualla Bilgin Aksu (Anı Publishing, 2018)
The purpose of this research is to inquire views of the school administrators on their own professional development and their leadership behaviours for the school improvement. A qualitative research with a phenomenological design was employed. Study group consisted of twelve high school administrators selected in accordance with two accepted criteria through maximum variation within purposive sampling technique. Participants were chosen among administrators with at least a three year experience in their administrative position, and through the maximum variation sampling in terms of the demographic variables seniority and working in different education regions. Data were collected by means of a semi-structured interview, and were analyzed with the content analysis method in this study. The interview questions were developed by the researchers in accordance with the research questions. The result of the study revealed that the school administrators defined professional development similarly to the definitions in related literature. Administrators' professional development needs were classified within four following sub-themes: knowledge about management, personal development, technical proficiency, and school-community relations. Administrators provided their professional development by means of publications, meetings, resource persons, academic studies. Collegiality, was emphasized for providing sustainability in administrators' professional development. Leadership behaviours of the administrators on the school improvement as a part of professional development were classified within three sub-themes: governance, personal development, and influence. However, this study has some limitations in terms of not only research design but also its participants. Therefore, further research is needed in the future.